2004
DOI: 10.1002/lt.20311
|View full text |Cite
|
Sign up to set email alerts
|

Liver transplantation outcomes for early-stage hepatocellular carcinoma: Results of a multicenter study

Abstract: The incidence of hepatocellular carcinoma (HCC), a frequent and incurable complication of cirrhosis, continues to rise. Orthotopic liver transplantation (OLT) has been proposed as a treatment for unresectable, intrahepatic HCC limited in extent to the Milan criteria adopted by the United Network of Organ Sharing (UNOS) in 1998. More recently, somewhat less restrictive University of California, San Francisco (UCSF) 10 , criteria were proposed. To examine the long-term outcomes of OLT for HCC patients and to ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
102
2
2

Year Published

2005
2005
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(119 citation statements)
references
References 17 publications
13
102
2
2
Order By: Relevance
“…39,63,77 In agreement with the proven role of AFP as a prognostic tool (rather than a diagnostic tool) for HCC, high serum levels of AFP have been correlated with a deterioration in the prognosis of patients with tumors belonging to the MC category, even though a precise cutoff is missing (Table 3). Although the strength of the evidence is impoverished by the suboptimal quality (average NOS score ¼ 6) and the limited number of studies, 12,18,20,24,35,36,[38][39][40]51,54,65,80 AFP in clinical practice represents a quite reliable and noninvasive tool for capturing potentially more aggressive HCCs within the MC. In some centers, values > 400 or >1000 ng/mL are often important determinants for delisting patients otherwise eligible for LT. 24,119,120 4.…”
Section: In Comparison With Patients With Hccs Exceed-mentioning
confidence: 60%
See 3 more Smart Citations
“…39,63,77 In agreement with the proven role of AFP as a prognostic tool (rather than a diagnostic tool) for HCC, high serum levels of AFP have been correlated with a deterioration in the prognosis of patients with tumors belonging to the MC category, even though a precise cutoff is missing (Table 3). Although the strength of the evidence is impoverished by the suboptimal quality (average NOS score ¼ 6) and the limited number of studies, 12,18,20,24,35,36,[38][39][40]51,54,65,80 AFP in clinical practice represents a quite reliable and noninvasive tool for capturing potentially more aggressive HCCs within the MC. In some centers, values > 400 or >1000 ng/mL are often important determinants for delisting patients otherwise eligible for LT. 24,119,120 4.…”
Section: In Comparison With Patients With Hccs Exceed-mentioning
confidence: 60%
“…99 Indeed, in 9 studies, patients with chronic hepatitis and cirrhosis who met the MC and underwent LT for HCC achieved posttransplant survival rates comparable to those of patients with nontumor indications for LT. Although they were not designed to specifically address a survival equivalence between LT patients within the MC and LT patients with nontumor indications, 4 prospective cohort studies (level 1b) 2,10,11,13 and 5 retrospective cohort studies 29,32,39,45,46 (level 2b) reported 5-year survival rates of 65% to 78% for patients meeting the MC and 68% to 87% for patients with nontumor indications. The European Liver Transplant Registry, the Organ Procurement and Transplantation Network, and the Australian and New Zealand Liver Transplant Registry 100-102 have confirmed survival rates of 70% to 82% for patients with nontumor indications.…”
Section: And Nontumor Indicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Factors associated with tumor recurrence include tumor burden and vascular invasion. 4,5,7,9,[11][12][13][14][15][16][17] Recurrence tends to occur in 6.4% to 21.2% of patients 8,9,11,12 ( Table 1). The 5-year patient survival rate after HCC recurrence is only 22%.…”
Section: Introductionmentioning
confidence: 99%